Metaphorical Perceptions of Prospective Teachers Regarding the Concept of Digital Literacy - Aysel Arslan; Mevlüde Sümeyye Polat (Journal of Pedagogy and Education Science, 2026)
This study aims to reveal prospective teachers’ perceptions of the concept of “digital literacy” through metaphors. The study was conducted using a phenomenological research design and carried out with 45 prospective teachers studying at Sivas Cumhuriyet University during the 2024–2025 academic year. The data were collected through an open-ended metaphor form, asking participants to complete the statement “Digital literacy is like… because…”. The responses were analyzed using content analysis. A total of 45 metaphors were obtained, and the most frequently used metaphors were book, knowledge, and real literacy. The metaphors were grouped under five categories: Education, Technology, Abstract, Tool/Object, and Nature, with Education being the most concentrated category. The findings indicated that prospective teachers largely associate digital literacy with accessing information, learning, understanding, and using technology consciously. In conclusion, prospective teachers view digital literacy as an essential skill in modern life, a fundamental resource for accessing information, and a multidimensional domain that needs to be managed carefully. This study offers insights for enhancing prospective teachers’ cognitive and pedagogical awareness regarding digital literacy.